Effects of Dietary Glycerol Monobutyrate Supplementation on Egg Performance, Biochemical Indices, and Gut Microbiota of Aged Hens - Xiao, Gengsheng; Zheng, Liwei; Yan, Xia; Yang, Yang; Qi, Qien; Gong, Li; Zhang, Huihua (Frontiers in Animal Science, 2022)
The purpose of this experiment was to determine the effect of dietary supplementation with glycerol monobutyrate (GMB) on egg laying performance, biochemical indicators and gut microflora at the late stage of laying hens. Total of 252 healthy Dawu Golden Phoenix laying hens with no difference in body weight were selected and randomly divided into two groups: 1) control group (CG), corn-soybean meal diet, 2) 500 mg glycerol monobutyrat / kg added to the basal diet. Six replicates were set up for each treatment group, with 21 birds per replicate. The trial started at week 55 and lasted for 8 weeks. Compared to the control group, the supplementation with GMB significantly increased egg weight, shell thickness and decreased egg breaking rate (P < 0.05). There was no significant difference in egg production rate, feed-to-egg ratio, egg shape index, egg shell strength and Haugh unit between two groups. In addition, dietary GMB significantly decreased the levels of aspartate aminotransferase and total bilirubin in serum, and significantly increased total antioxidant capacity and total superoxide dismutase (P < 0.05). However, alpha diversity indices (Ace, Chao1, Shannon, Simpson, goods_coverage, and PD_whole tree) were not different between the two groups. Notably, dietary GMB significantly decreased the abundances of Proteobacteria at phylum level and the abundances of Enterobacter at genus level (P < 0.01), but there was no significant difference in the composition of other cecal microbiota. In summary, the present study revealed that supplementation with 500 mg/kg glycerol monobutyrate increased egg weight and improved eggshell quality, but had limited effect on cecal microbial composition in the late stage of laying hens.